Impact of psychrometry on the aerosol distribution pattern in human lungs - Dhaundiyal, Alok; Albrecht, Gábor (Monte Carlo methods and applications, 2025)
This article investigates the localized air quality of the workplace and its impacts on the stochastic behaviour of aerosol deposition. Related to the same, the dewpoint (DPT), wet bulb (WBT) and dry bulb (DBT) temperatures, vapour pressure, and relative and specific humidities of the air are being tested. The given problem investigates the regional and total deposition of aerosol particles in the extrathoracic (Ex), bronchioles (Br) and alveolar sacs (A) of the subjects working in the bioenergy plant. The oral and nasal (n) pathways were considered for the air to enter the extrathoracic region of the human body. The algorithm based on the Monte-Carlo technique is written on Rust version 1.79.0 to calculate the deposition fraction of aerosol particles in the human lungs. The particle is assumed to have a spherical geometry. Only the diffusion of water vapour onto the surface of aerosol is the limiting factor for the growth of aerosol particles and the surface reaction is omitted. The deposition fraction of smaller-sized particles was seen to be increased with nucleation in the Ex region. Similarly, the change in the dew point of air also favoured the likelihood of deposition of the aerosol particle in the Ex region. As compared to the nasal pathway, the accretion of aerosol particles in the Ex region through the oral pathway declined by 35.12  to 38.33  owing to the growth of the aerosol particles with time.